Dynamic changes and importance of plasma concentrations of ether phospholipids, of which the majority are plasmalogens, in postpartum Holstein dairy cows - Saito, Risa; Kubo, Tomoaki; Wakatsuki, Takuji; Asato, Yuuki; Tanigawa, Tamako; Kotaniguchi, Miyako; Hashimoto, Maki; Kitamura, Shinichi; Kadokawa, Hiroya (Reproduction fertility and development, 2023)
Ethanolamine plasmalogens (EPls) and choline plasmalogens (CPls) are classes of ethanolamine ether phospholipids (ePE) and choline ether phospholipids (ePC), respectively. EPls play crucial roles in maternal and breastfed infant bodies and stimulate gonadotropin secretion by gonadotrophs. To estimate changes in and importance of plasma concentrations of EPls and CPls, utilising newly developed enzymatic fluorometric assays for ePE and ePC in postpartum Holstein cows. Plasma samples were collected from 3weeks before expected parturition until approximately 8weeks after parturition (16 primiparous and 38 multiparous cows) for analysis. Plasma concentrations of ePE and ePC, most of which are plasmalogens, declined before and increased after parturition and stabilised near the day of the first postpartum ovulation (1stOV). From weeks 2 to 3 after parturition, third-parity cows exhibited ePE concentrations that were higher than those of other parity cows. The days from parturition to 1stOV correlated with days from parturition to conception. On the day of 1stOV, milk yield correlated with plasma concentration of both ePE and ePC, while ePC concentration correlated negatively with milk fat percentage. At the early luteal phase after 1stOV, plasma ePE concentration correlated with plasma anti-Müllerian hormone concentration (r =0.39, P <0.01), and plasma ePC concentration correlated with plasma follicle-stimulating hormone concentration (r =0.43, P <0.01). The concentrations of ePE and ePC changed dramatically around parturition and 1stOV, and the concentrations correlated with important parameters for milk production and reproduction. The blood plasmalogen may play important roles in postpartum dairy cows.